2007
DOI: 10.1128/mcb.00339-07
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Sox4 Expression in Oligodendrocytes Interferes with Normal Myelination in the Central Nervous System

Abstract: The highly related transcription factors Sox4 and Sox11 are both expressed in oligodendrocyte precursors. Yet whether they have a function in oligodendrocyte development is unknown. By overexpressing Sox4 under the control of 3.1 kb of 5 flanking sequences of the myelin basic protein gene in transgenic mice, we extended Sox4 expression in the oligodendrocyte lineage from oligodendrocyte precursors to cells undergoing terminal differentiation. As a consequence of transgene expression, mice develop the full spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 27 publications
5
45
0
Order By: Relevance
“…In these experiments, neuronal specification remained unaltered, but specified precursors prematurely expressed pan-neuronal differentiation markers. Our own transgenic overexpression studies of Sox4 in different glial lineages of the CNS had pointed to a role of SoxC proteins in maintenance of the glial precursor state and/or prevention of terminal differentiation (Hoser et al, 2007;Potzner et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these experiments, neuronal specification remained unaltered, but specified precursors prematurely expressed pan-neuronal differentiation markers. Our own transgenic overexpression studies of Sox4 in different glial lineages of the CNS had pointed to a role of SoxC proteins in maintenance of the glial precursor state and/or prevention of terminal differentiation (Hoser et al, 2007;Potzner et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of SoxC proteins and knockdown by siRNA nevertheless suggest that neural functions exist. Neural tube electroporations in chicken embryos indicated that Sox4 and Sox11 promote the acquisition of panneuronal properties in precursors of CNS neurons (Bergsland et al, 2006), and transgenic overexpression in the mouse has provided evidence for a negative influence on the differentiation of CNS glia (Hoser et al, 2007;Potzner et al, 2007). Available data thus point to an influence of SoxC proteins on differentiation events.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the SoxC family in neuronal development is not fully understood and it was suggested that SoxC proteins control the establishment of pan-neuronal gene expression (Bergsland et al, 2006) in contrast to proneural bHLH proteins that have been linked to the control of neuronal subtype identity (Berninger et al, 2007). However, Sox4 and Sox11 might also have other functions as they are expressed during other adult differentiation programs, such as in oligodendrocytes, lymphocytes, pancreatic beta cells and osteoblasts (Kuhlbrodt et al, 1998;Potzner et al, 2007;Penzo-Mendez, 2010), in many malignancies and behave as oncogenes (Ikushima et al, 2009;Scharer et al, 2009). Taken together, proneural bHLH and SoxC TFs-while both are involved in neuronal fate determination and differentiation-seem to be regulated by a distinct temporal pattern of PcG-mediated repression.…”
Section: Dynamic Control By Pcg and Trxg Groupmentioning
confidence: 99%
“…Other phenotypic defects at the time of death include dysgenesis of the anterior eye segment, various cranial and noncranial skeletal malformations, persistent herniation of the gut, asplenia, and hypoplasia of several other organs including the stomach, the pancreas, and the lung (25,35). In the developing nervous system, Sox4 and Sox11 have largely redundant functions in the establishment of neuronal properties (1) and in glial maturation (8,11,17).…”
mentioning
confidence: 99%